Les Banū Thaʻlaba, une famille andalouse à Fès (iiie/ixe-ive/xe siècle) - Aurélien Montel (Revue des Mondes Musulmans et de la Méditerranée)
Abstract: The story of Banū Thaʻlaba family of Fez (iiie/ixe-ive/xe centuries). This paper relates the story of a prominent family of Fez settled from al-Andalus, the Banū Thaʻlaba, which are mentioned by various medieval sources. First, it aims at profile the members of this family compilating quick biographical data about them, in order to illustrate and understand the permanence of this family at the highest levels of society. Then, the study of the Banū Thaʻlaba will lead to some more general reflexions about the society of this time, particularly on the integration of Andalusian at the Maghreb al-Aqṣā’ urban elites.